Psychologically informed practice (PIP) within the offender personality disorder pathway: Towards establishing an evidence base for approved premises. (4th August 2020) - Bruce, Matthew; Patel, Shivani; Stevens, Peter
Abstract: The United Kingdom (UK) government has commissioned numerous interventions across all stages of the criminal justice pathway for managing offenders likely to have a personality disorder, with the intention to reduce reoffending, improve psychological wellbeing, and develop workforce capabilities. Psychologically Informed Practice (PIP) models underpin these. To evaluate a modified PIP model within the post‐imprisonment community stage of the Offender Personality Disorder (OPD) pathway, specifically workforce development, within all London (UK) probation supervised hostels (approved premises), we used both non‐equivalent control group and pre‐post repeated measure designs to compare changes in staff and offender outcomes before and after introduction of a PIP model across all 12 London approved premises. Findings revealed statistically significant improvements in a number of workforce outcomes (measured using the Personality Disorder ‐ Knowledge, Attitudes and Skills Questionnaire and Maslach Burnout Inventory) which were moderated by age and gender. Data did not support associated improvements in resident offender outcomes (progressive moves, rearrests/reoffences, or breaches leading to recalls). The modified PIP is an effective intervention model for improving some workforce outcomes among probation supervised hostel staff, particularly for women, but our findings suggest that intervention development may be required for significant improvements to be observed in resident offending outcomes. In addition, further research is necessary to determine the longer term effects of PIP on absenteeism, employee turnover, quality of resident‐staff interactions, and overall culture change among staff working within the post‐imprisonment community stage of the OPD pathway.